Retrospective Evaluation of Clinical and Molecular Characteristics of Patients with Fabry Disease Being Followed-Up in Our Clinic - KASAPKARA, Çiğdem Seher; OLGAC, Asburce; YILDIZ, İsmail; KASAPKARA, Hacı Ahmet; KILIÇ, Mustafa (Turkish Journal of Pediatric Disease, 2021)
Abstract:Objective: Fabry disease (FD) is an X-linked lysosomal storage disease (LSD), that occurs due to deficient activity of the enzyme alpha-galactosidase A (a-GalA) with multisystemic involvement. The disease can present with a wide range of symptoms, from mild form to the severely affected classical male phenotype with early organ failure and associated morbidity and mortality.Methods: Patients diagnosed with FD at Dr. Sami Ulus Maternity and Child Health Training and Research Hospital were enrolled. Phenotypic and genotypic presentations of 10 cases from three unrelated families have been evaluated. Diagnoses of relatives of index patients were reached by family screening. Clinical, laboratory and molecular genetic analysis of patients were collected.Results: A total of 10 patients including 7 males, (mean age 31.8, range: 14-59 years) and 3 females, (mean age 44.6, range: 40-51 years) were evaluated. Various multisystem manifestations were observed, including cardiac, neurological, cerebrovascular and ophtalmological involvement. Eight out of ten patients had hypohydrosis, 4/10 had angiokeratomas and hearing loss. All male and female patients had abdominal pain and 9/10 had neuropathic pain. Among 7 male patients, 6 had renal complications and 2 of them reached end stage renal disease (ESRD) requiring renal replacement therapy. Concentric left ventricular hypertrophy, was the most common echocardiographic finding along with mitral regurgitation. Conclusion: ERT may slow down the progression of disease if inititated early. To ensure early diagnosis, it is important to recognize the symptoms of FD. Family screening may help patients to be identified at the presymptomatic phase of the disease. That’s why the awareness of pediatricians should be increased about Fabry Disease. Giriş: Fabry Hastalığı (FH), X’e bağlı geçiş gösteren bir lizozomal depo hastalığı olup, GLA geninde meydana gelen bozukluklara bağlı olarak ortaya çıkmaktadır. Lizozomal alfa-galaktozidaz A (a-Gal-A) enzimindeki etkilenme nedeniyle bazı sfingolipidler çeşitli dokularda birikmekte ve hayati organlarda klinik bulgulara neden olmaktadır. Hastalığa bağlı başlıca klinik bulgular; akroparesteziler, anjiokeratomlar, kornea vertisillata, gastrointestinal, renal, kardiyak ve nörolojik etkilenmedir. Hastalığın tedavisinde enzim replasman tedavisi ve şaperon tedavilerinden faydalanılmaktadır. Yöntem: Bölümümüzde takip edilmekte olan 10 Fabry hastası çalışmaya dahil edildi. Hastalara ait kayıtlar retrospektif olarak, hastane kayıtlarından elde edildi. Hastaların klinik ve genetik özellikleri incelendi. Tam kan sayımı, biyokimya lyso-Gb3, AGALA düzeyleri, idrar analizi, GLA gen mutasyonları, odyometrik ve oftalmolojik bulgular, ekorkardiyografi ve beyin manyetik rezonans (MR) görüntüleme sonuçları kaydedildi. Tüm hastalardan yazılı onam alındı. Bulgular: 10 Fabry hastasının (7 erkek, 3 kadın) özellikleri incelendi. Hastalarda başta kardiyak, serebrovasküler ve oftalmolojik olmak üzere çok çeşitli klinik bulgular tespit edildi. 6/10 hastada terleme azlığı ve karın ağrısı, 7/10 anjiokeratomlar, 4/10işitme kaybı, 9/10 nöropatik ağrı mevcuttu. 6/7 erkek hastada hastalığa bağlı renal komplikasyonlar tespit edildi. 2/10 hastada ciddi kardiyak hadise öyküsü mevcuttu. 2/3 kadın hastada proteinüri ve hipertansiyon, 1/3 kadın olguda oftalmolojik bulgular, 2/3 anjiokeratom tespit edildi. En sık saptanan ekokardiyografik bulgular sol ventrikül hipertrofisi ve mitral yetmezlikti. 2 hastada beyin MR incelemede periventriküler gliosis ve laküner enfarkt alanları mevcuttu. Eşlik eden komorbid durumlar arasında FMF, anklozan spondilit ve çölyak hastalığı mevcuttu. Sonuç: FH semptomlarının erken yaşta tanınması ve tedaviye erken dönemde başlanabilmesi prognoz açısından oldukça önemlidir. Bu nedenle, çocuk hekimlerinin multisistemik tutulum gösteren FH ile ilgili farkındalıklarının artırılması gerekmektedir. Anahtar kelimeler: Alfa-galaktozidaz A, multisistemik tutulum, Fabry hastalığı